AIP Conference Proceedings 2009
DOI: 10.1063/1.3222889
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescent Features and Raman Spectroscopy of Miocene Hydrothermal Bio-mineralization Embedded in Cryptocrystalline Silica Varieties, Central Europe, Hungary

Abstract: Abstract. Variable cryptocrystalline silica varieties occur en masse in the fractures and cavities of the andesite host rock, showing different genetic and morphological features of variable microbial activity. Four types of CL features characterized silica phases. Raman spectroscopy supported variable amorphous carbon phases in inhomogenous distribution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…(Hungary), in the neighborhood of Gyöngyöstarján, variable cryptocrystalline silica varieties occur together with iron mineralization in fractures and cavities of an andesite host rock (Czakó and Zelenka 1981). The genesis is related to the near surface interaction of microbial activities with an inorganic hydrothermal vent system (Müller et al 2009b). The fine-grained silica matrix, consisting of cryptocrystalline quartz with traces of moganite and opal-CT, is characterized by bright yellow CL (sample CQMa, Fig.…”
Section: Sample Materialsmentioning
confidence: 98%
See 1 more Smart Citation
“…(Hungary), in the neighborhood of Gyöngyöstarján, variable cryptocrystalline silica varieties occur together with iron mineralization in fractures and cavities of an andesite host rock (Czakó and Zelenka 1981). The genesis is related to the near surface interaction of microbial activities with an inorganic hydrothermal vent system (Müller et al 2009b). The fine-grained silica matrix, consisting of cryptocrystalline quartz with traces of moganite and opal-CT, is characterized by bright yellow CL (sample CQMa, Fig.…”
Section: Sample Materialsmentioning
confidence: 98%
“…There are a few reports from hydrothermal sulfide ore deposits (e.g., Moura et al 2003;Drechsel et al 2003;Ioannou et al 2003) and hydrothermal gold deposits (e.g., Graupner et al 2000;Takahashi et al 2008;Gueye et al 2013), where the yellow luminescent quartz was mostly detected in late mineralization sequences. In addition, quartz with yellow CL occurs in agate, silicified wood and hydrothermal veins related to mineralization and alteration processes in volcanic rocks (Götze et al 1999;Götze and Rössler 2000;Möckel and Götze 2007), as well as hydrothermal biomineralization (e.g., Müller et al 2009b). Sometimes, yellow luminescent quartz is associated with quartz showing transient blue CL, which is characteristic for quartz crystallized from low-temperature aqueous solutions (compare Figs.…”
Section: Introductionmentioning
confidence: 95%
“…Altered rocks and sediments in oceans as well as in surface and subsurface environments are the most common and widely distributed habitats of bacteria in geological settings. Numerous studies have shown that both rock alteration and mineral formation due to microbial activities are possible, even under extreme conditions [76][77][78][79]. In particular, the common tubular alteration of The detailed morphometric analysis revealed that the typical micro-textures observed in the filamentous fabrics from the MDP are clearly distinct from similar types of non-biological aggregates such as fibrous minerals, speleothems (stalactite-type) or inorganic precipitates similar to "chemical gardens" [69][70][71].…”
Section: Biogenic Origin and Formation Mechanism Of Sffmentioning
confidence: 99%
“…Altered rocks and sediments in oceans as well as in surface and subsurface environments are the most common and widely distributed habitats of bacteria in geological settings. Numerous studies have shown that both rock alteration and mineral formation due to microbial activities are possible, even under extreme conditions [76][77][78][79]. In particular, the common tubular alteration of basaltic glass in submarine environments was attributed by several authors to microbial boring as euendoliths and interpreted as evidence of biogenicity, but this was also critically debated [80][81][82][83][84][85][86].…”
Section: Biogenic Origin and Formation Mechanism Of Sffmentioning
confidence: 99%
“…Müller et al [220] found Fe-rich cryptocrystalline silica masses with agate-like structures in the southern part of the Mátra Mts. (Hungary), in the neighbourhood of the Gyöngyöstarján and Gyönggyösoroszi area (Figure 34f).…”
Section: Microstructural Peculiarities and Possible Biosignatures In Agatesmentioning
confidence: 99%